ANALISIS HUKUM TERHADAP PERTIMBANGAN HAKIM DALAM MENJATUHKAN HUKUMAN PELAKU TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA YANG MENGAKIBATKAN LUKA BERAT - Rini Putri Ndruru (Jurnal Panah Hukum, 2025)
If a family member is both the perpetrator and victim of domestic violence, then this is considered a form of domestic violence that occurs in the home. Those who are mothers, fathers, husbands, partners, or even domestic workers can become victims of domestic violence. 992 K/Pid.Sus/2017 is the Supreme Court case number for one of the domestic violence cases being investigated and tried. Because he was accused of violating Article 44 paragraph (2) of Law of the Republic of Indonesia Number 23 of 2004 concerning the Elimination of Domestic Violence, the perpetrator was sentenced to one year in prison. The statutory approach, case approach, comparative approach, and analytical methods are all used in this type of normative legal research. Secondary data obtained from library sources, including primary and secondary law books, was used to collect data. Deductive reasoning is used to arrive at conclusions from qualitative descriptive data analysis. Based on a review of the research findings and discussion, it was concluded that the judge's consideration of Article 351 paragraph (2) which reads, "If the act results in serious injury, the guilty person is threatened with a maximum prison sentence of five years." “—if imposing punishment on perpetrators of domestic violence (study decision number 992 K/Pid.Sus/2017) is appropriate. The author argues that in deciding a criminal case, the panel of judges must be more careful in ensuring that the punishment imposed on the offender is in accordance with applicable law.